Research Progress on the Mechanisms of Acupoint Catgut Embedding and Related Materials - Li, Xinyi; Wei, Wan; Zhou, Yingdong; Huang, Mengyang; Gao, Lin; Wei, Shanshan; Zheng, Ani; Zhang, Chunyan (Journal of Contemporary Medical Practice, 2025)
By searching in China Knowledge Network, PubMed, with the search time from September 2014 to September 202, and by using "acuoint catgut embedding" as the key words in English, a of more than 3000 documents were retrieved in the past 10 years. By summarizing and analyzing, it was found that among the many methods acupuncture, acuoint catgut embedding therapy has the advantages of long stimulation time, less treatment times and wide clinical application. In recent years, the and innovation of embedded materials have been continuing, and it is expected to play a similar role as the previous sheep intestinal thread in the treatment of diseases, which can the treatment of part of the patients who are allergic to sheep intestinal thread. The mechanism of the material of acuoint catgut embedding is also very important the development of new high molecular acuoint catgut embedding materials. This article will discuss the introduction of high molecular acuoint catgut embedding materials, research, and the application of new embedding materials, etc., so as to provide ideas for the development and selection of new acuoint catgut embedding materials mechanism research in the future.